ENHANCING CHILDREN’S SAFETY AND WELLBEING: EXPLORING THE ROLE OF A NEW SOCIAL SERVICE PROGRAMME IN FREE STATE TOWNSHIP SCHOOLS - Reyneke, Roelf (Social Work/Maatskaplike Werk, 2024)
In response to the pervasive violence affecting children's psychosocial wellbeing in South Africa, the Adopt-a-School Foundation introduced the Thari programme, targeting behavioural challenges that manifest in gangs, substance abuse and classroom disruptions. This article presents findings from a pilot project in Botshabelo, Free State, where gangsterism, academic struggles and social issues prevailed. The main study used an exploratory sequential mixed-methods design (qualitative/quantitative), but this article reports only on a part of the qualitative data from group and individual interviews that explored participants' perspectives. The study focused on children's behavioural challenges and observed school changes during implementation of the Thari programme. Results show a notable reduction in gangsterism and psychosocial issues, leading to decreased disruptive behaviour among children and highlighting improved behaviour after the introduction of psychosocial services.